PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PIZZA HUT DELIVERY TANGERANG SELATAN - Noto Susanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Performing means achieving the expected work results and the work process is in accordance with applicable procedures. The positive side of why performance needs to be strived for is because performance has an impact on organizational maturity in achieving its goals. Based on this background, the purpose of this study was to determine the effect of work environment and work motivation on employee performance at the PHD South Tangerang Branch, either partially or simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample in this study was 74 respondents. Methods of data analysis using simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results of the study suggest that the environment and motivation are factors that have a positive influence on employee performance. Because these two factors can encourage the birth of work enthusiasm, which has implications for the implementation of good work and the achievement of satisfactory work results.